Christmas with Southern Living 2022 : inspired ideas for holiday cooking & decorating. (Southern Living Books, 2022)
Offers recipes for meals, treats, and baked goods for gift-giving and holiday entertaining, along with seasonal decorating ideas, including festive centerpieces, mantels, and wreaths.